Monetary policy and unemployment: The US, Euro-area and Japan - Willi Semmler (Routledge, 2005)
This book pulls together papers presented at a conference in honour of the 1981 Nobel Prize Winner for Economic Science, the late James Tobin. Among the contributors are Olivier Blanchard, Edmund Phelps, Charles Goodhart and Marco Buti. One of the main aims of the conference was to discuss what potential role monetary policy has on economic activity and unemployment reduction in three key currency zones - the United States, European Union and Japan.
Keywords: 330; output gap; real interest rate; Taylor Rule; central bank; Geldpolitik; Arbeitslosigkeit; EU-Staaten; USA; Japan